Casting powder for low-carbon free-cutting steel and production method of low-carbon free-cutting steel small square billet

CN119772123APending Publication Date: 2025-04-08SGIS SONGSHAN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510004812.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

[0003]由于易切削钢热收缩系数相对较大、凝固坯壳收缩量较大,如果保护渣不能控制铸坯与结晶器之间的传热,则易导致铸坯表面凹陷缺陷的形成

Benefits of technology

[0025]本申请中,为了使得易切削钢用保护渣能够减缓铸坯向结晶器的传热,使铸坯坯壳横向结晶器传热的同时自身不产生表面凹陷缺陷,有利于实现铸坯坯壳均匀生长和减缓传热的目的,提高生产出的易切削钢铸坯表面质量合格率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226539100000081
    Figure BDA0005226539100000081
  • Figure BDA0005226539100000082
    Figure BDA0005226539100000082
  • Figure BDA0005226539100000091
    Figure BDA0005226539100000091
Patent Text Reader

Abstract

The invention discloses casting powder for low-carbon free-cutting steel and a production method of a small square billet of the low-carbon free-cutting steel. The melting point of the casting powder ranges from 1200 DEG C to 1300 DEG C, the melt weight ranges from 0.6 g / ml to 0.95 g / ml, the viscosity ranges from 1.3 pa.s to 1.8 pa.s, and the alkalinity ranges from 0.60 to 0.80. According to the casting powder for the free-cutting steel, the casting powder for the free-cutting steel can slow down heat transfer from a casting blank to a crystallizer, so that a casting blank shell does not generate the surface sunken defect while transferring heat transversely to the crystallizer, the purposes of uniform growth of the casting blank shell and slow down heat transfer are achieved, and the surface quality qualification rate of the produced free-cutting steel casting blank is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steelmaking, in particular to a method for producing protective slag for low-carbon free-cutting steel and a low-carbon free-cutting steel billet. Background Art

[0002] The C content of free-cutting steel is between 0.03% and 0.08%, which is a sub-peritectic steel. When casting sub-peritectic steel, the primary shell near the meniscus of the crystallizer undergoes a peritectic reaction of δFe→γFe as the temperature drops, accompanied by linear shrinkage and volume shrinkage. The primary shell separates from the copper plate to form an air gap, resulting in the minimum heat flow and the thinnest shell, which leads to the formation of depressions and bubbles on the surface of the small square billet. In addition, the S content in the steel is high and the crack sensitivity is strong.

[0003] Since the thermal shrinkage coefficient of free-cutting steel is relatively large and the solidified billet shell shrinks a lot, if the protective slag cannot control the heat transfer between the billet and the crystallizer, it is easy to cause the formation of concave defects on the billet surface. The existing protective slag for low-carbon free-cutting steel has a low melting point and low viscosity. The protective slag melts too quickly, and the heat loss of the molten steel is large, causing the local molten steel in the upper cross section of the crystallizer to be overcooled. The corresponding billet shell should shrink and form pit defects.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a protective slag for low-carbon free-cutting steel and a production method of a low-carbon free-cutting steel billet, so as to reduce the incidence of surface depression of the billet.

[0006] The present invention is achieved in that:

[0007] In the first aspect, the present invention provides a protective slag for low carbon free-cutting steel, comprising the following components in weight percentage: SiO2 28wt%-35wt%, CaO 20wt%-26wt%, MgO 3wt%-6.5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 12wt%-15wt%, R2O 3.6wt%-3.7wt%, F2.5wt%-5.5wt%, C 11wt%-12wt% and H2O0.1wt%-0.35wt%, R2O is an oxide of alkali metal, and the melting point of the protective slag is 1200℃-1300℃, the melt weight is 0.6g / ml-0.95g / ml, the viscosity is 1.3pa.s-1.8pa.s, and the basicity is 0.60-0.80.

[0008] In an optional embodiment, the following components are included in weight percentage: SiO2 30wt%-35wt%, CaO 20wt%-25wt%, MgO 4wt%-5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 13wt%-14wt%, R2O 3.05wt%-3.95wt%, F 3.8wt%-4.2wt%, C 11wt%-12wt% and H2O 0.28wt%-0.32wt%. The protective slag has a melting point of 1248°C-1252°C, a melt weight of 0.84g / ml-0.86g / ml, a viscosity of 1.63pa.s-1.67pa.s and a basicity of 0.65-0.75.

[0009] In an optional embodiment, the following components are included in weight percentage: SiO2 33wt%, CaO23wt%, MgO4.5wt%, Fe2O3 0.7wt%, Al2O3 13.5wt%, R2O 3.65wt%, F4.0wt%, C 11.5wt% and H2O0.30wt%, and the protective slag has a melting point of 1250°C, a melt weight of 0.85g / ml, a viscosity of 1.65pa.s and a basicity of 0.7.

[0010] In a second aspect, the present invention provides a method for producing low-carbon free-cutting steel billets, comprising converter smelting, LF refining and continuous casting of billets using the protective slag described in any one of the aforementioned embodiments.

[0011] In an optional embodiment, the low carbon free-cutting steel comprises, by weight percentage: C 0.03wt%-0.08wt%, Si≤0.08wt%, Mn 1.1wt%-1.5wt%, P 0.05wt%-0.10wt%, S 0.20wt%-0.40wt%, Cu+Ni+As+Sn+Pb≤0.5wt%, and the balance is iron and unavoidable impurities.

[0012] In an optional embodiment, in the continuous casting step, the tundish baking parameters are: low fire time ≥90 min, medium fire time ≥0 min, high fire time ≥60 min, insulation time ≥60 min, and total time 3.0 h-4.5 h.

[0013] In an optional embodiment, in the continuous casting step, the vibration stroke of the crystallizer is 8 mm-10 mm, and the vibration frequency of the crystallizer is (79-81)*V times / min, wherein V is the pulling speed and the unit of the pulling speed is m / min.

[0014] In an optional embodiment, the continuous casting step satisfies at least one of the following features af:

[0015] a. The taper of the copper tube of the crystallizer is 0.15% / m-0.20% / m;

[0016] b. Crystallizer cooling water flow rate is 105Nm 3 / h-120Nm 3 / h;

[0017] c. The water gap of the crystallizer is controlled to be 4.0mm-4.5mm;

[0018] d. The immersion nozzle adopts an integral type, the centering deviation between the immersion nozzle and the crystallizer is ≤±5mm, and the insertion depth of the immersion nozzle is 90mm-130mm;

[0019] e. Crystallizer electromagnetic stirring parameters are 200-300A / 3Hz;

[0020] f. The terminal electromagnetic stirring parameters are 300-400A / 8Hz.

[0021] In an optional embodiment, the C content of the converter argon station is 0.04%-0.06%, and the free oxygen control range of the argon station is 30ppm-80ppm;

[0022] And / or, the C content at the converter end point is greater than 0.08%, and the C content is adjusted to 85%-92% of the target C content during the steel tapping process.

[0023] In an optional embodiment, the surface pit and bubble defect rate of the prepared small square billet is less than 0.5%.

[0024] The present invention has the following beneficial effects:

[0025] In the present application, in order to enable the protective slag for free-cutting steel to slow down the heat transfer from the ingot to the crystallizer, the ingot shell can transfer heat horizontally to the crystallizer without producing surface depression defects, which is beneficial to achieve the purpose of uniform growth of the ingot shell and slowing down heat transfer, and improve the surface quality pass rate of the produced free-cutting steel ingots. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0027] An embodiment of the present invention provides a protective slag for low carbon free-cutting steel, which includes the following components in weight percentage: SiO2 28wt%-35wt%, CaO 20wt%-26wt%, MgO 3wt%-6.5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 12wt%-15wt%, R2O 2wt%-5wt%, F2.5wt%-5.5wt%, C 11wt%-12wt% and H2O0.1wt%-0.35wt%, R2O is an oxide of alkali metal, and the melting point of the protective slag is 1200℃-1300℃, the melt weight is 0.6g / ml-0.95g / ml, the viscosity is 1.3pa.s-1.8pa.s, and the basicity is 0.60-0.80.

[0028] In the present application, in order to enable the protective slag for free-cutting steel to slow down the heat transfer from the ingot to the crystallizer, the ingot shell can transfer heat horizontally to the crystallizer without producing surface depression defects, which is beneficial to achieve the purpose of uniform growth of the ingot shell and slowing down heat transfer, and improve the surface quality pass rate of the produced free-cutting steel ingots.

[0029] Specifically, in the protective slag provided in the present application: the SiO2 content is relatively high, which reduces the basicity of the protective slag; a carbonaceous material with a high calorific value is selected to increase the melting point of the protective slag and reduce the melting rate of the protective slag; the Al2O3 content is relatively high, which increases the viscosity of the protective slag and improves the surface tension of the protective slag, thereby reducing the pit and bubble defect rate on the surface of the small square billet; R2O is an oxide of an alkali metal such as sodium oxide, potassium oxide, etc.

[0030] For the protective slag of free-cutting steel, it is beneficial to select carbonaceous materials with high calorific value and control the melting rate to stabilize the three-layer structure; select a protective slag system with low basicity, slightly high melting point and viscosity to make the liquid slag flow evenly into the crystallizer gap, reduce longitudinal depressions and bubbles, and achieve the purpose of slow cooling of the primary shell.

[0031] In an optional embodiment, the following components are included in weight percentage: SiO2 30wt%-35wt%, CaO 20wt%-25wt%, MgO 4wt%-5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 13wt%-14wt%, R2O 3.05wt%-3.95wt%, F 3.8wt%-4.2wt%, C 11wt%-12wt% and H2O 0.28wt%-0.32wt%. The protective slag has a melting point of 1248°C-1252°C, a melt weight of 0.84g / ml-0.86g / ml, a viscosity of 1.63pa.s-1.67pa.s and a basicity of 0.65-0.75.

[0032] In an optional embodiment, the following components are included in weight percentage: SiO2 33wt%, CaO23wt%, MgO4.5wt%, Fe2O3 0.7wt%, Al2O3 13.5wt%, R2O 3.65wt%, F4.0wt%, C 11.5wt% and H2O0.30wt%, and the protective slag has a melting point of 1250°C, a melt weight of 0.85g / ml, a viscosity of 1.65pa.s and a basicity of 0.7.

[0033] Adjusting and optimizing the mold slag composition can help further reduce the pit and bubble defect rate on the surface of the small square billet.

[0034] An embodiment of the present invention further provides a method for producing low-carbon free-cutting steel billets, comprising converter smelting, LF refining and continuous casting of billets using the protective slag described in any one of the aforementioned embodiments.

[0035] In an optional embodiment, the low carbon free-cutting steel comprises, by weight percentage: C 0.03wt%-0.08wt%, Si≤0.08wt%, Mn 1.1wt%-1.5wt%, P 0.05wt%-0.10wt%, S 0.20wt%-0.40wt%, Cu+Ni+As+Sn+Pb≤0.5wt%, and the balance is iron and unavoidable impurities.

[0036] Low-carbon free-cutting steel has a low carbon content, which can reduce the hardness and strength of the steel, improve its plasticity and toughness, and facilitate cutting. Low-carbon free-cutting steel also contains elements such as manganese, phosphorus, and sulfur, which are beneficial to improving its cutting performance and mechanical properties.

[0037] In an optional embodiment, in the continuous casting step, the tundish baking parameters are: low fire time ≥ 90 min, medium fire time ≥ 0 min, high fire time ≥ 60 min, insulation time ≥ 60 min, and total time 3.0 h-4.5 h. Adjusting the tundish baking parameters is conducive to ensuring that the refractory material in the tundish is fully dried, reducing inclusions and pores in the molten steel, and improving the surface quality of the small square billet.

[0038] In an optional embodiment, in the continuous casting step, the vibration stroke of the crystallizer is 8 mm-10 mm, and the vibration frequency of the crystallizer is (79-81)*V times / min, wherein V is the pulling speed and the unit of the pulling speed is m / min.

[0039] If the vibration stroke of the crystallizer is too large or the frequency is too high, the impact force of the molten steel will increase, the fluctuation of the molten steel will increase, and the surface quality of the small square billet will be affected; if the vibration stroke of the crystallizer is too effective or the frequency is too low, the molten steel will flow unevenly in the crystallizer and increase surface defects.

[0040] In an optional embodiment, the continuous casting step satisfies at least one of the following features af:

[0041] a. The taper of the copper tube of the crystallizer is 0.15% / m-0.20% / m;

[0042] b. Crystallizer cooling water flow rate is 105Nm 3 / h-120Nm 3 / h;

[0043] c. The water gap of the crystallizer is controlled to be 4.0mm-4.5mm;

[0044] d. The immersion nozzle adopts an integral type, the centering deviation between the immersion nozzle and the crystallizer is ≤±5mm, and the insertion depth of the immersion nozzle is 90mm-130mm;

[0045] e. Crystallizer electromagnetic stirring parameters are 200-300A / 3Hz;

[0046] f. The terminal electromagnetic stirring parameters are 300-400A / 8Hz.

[0047] During the continuous casting process, unreasonable settings of parameters such as mold vibration stroke, vibration frequency, copper tube taper, cooling water flow, water gap, immersion nozzle and mold centering deviation, immersion nozzle insertion depth, electromagnetic stirring, etc. will lead to an increase in surface defects of small square billets, including cracks, vibration marks, pits, etc.

[0048] In an optional embodiment, the C content of the converter argon station is 0.04%-0.06%, and the free oxygen control range of the argon station is 30ppm-80ppm;

[0049] And / or, the C content at the converter end point is greater than 0.08%, and the C content is adjusted to 85%-92% of the target C content during the steel tapping process.

[0050] In an optional embodiment, the surface pit and bubble defect rate of the prepared small square billet is less than 0.5%.

[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0052] Example 1

[0053] The present embodiment provides a method for producing a low-carbon free-cutting steel billet, comprising converter smelting, LF refining and continuous casting; the low-carbon free-cutting steel comprises, by weight percentage, C 0.05wt%, Si 0.07wt%, Mn 1.3wt%, P0.07wt%, S 0.30wt%, Cu 0.04%, Ni 0.09%, As 0.08%, Pb 0.13%, Sn 0.09%, and the balance is iron and unavoidable impurities.

[0054] The C content at the converter argon station is 0.05%, and the free oxygen control range of the argon station is 60ppm; the C content at the converter end point is 0.09%, and the C content during the steelmaking process is adjusted to 90% of the target C content.

[0055] The composition and some indicators of the protective slag used in the continuous casting step are shown in Table 1. The tundish baking parameters are: low fire time 90min, medium fire time 30min, high fire time 60min, insulation time 60min, total time 4.0h-4.5h; the crystallizer vibration stroke is 9mm, the crystallizer vibration frequency is 80*V times / min, where V is the pulling speed, V=1.8m / min; the crystallizer copper tube taper is 0.18% / m; the crystallizer cooling water flow rate is 115Nm 3 / h; the water gap of the crystallizer is controlled to be 4.2mm; the immersion nozzle adopts an integral type, the alignment deviation between the immersion nozzle and the crystallizer is ≤±5mm, and the insertion depth of the immersion nozzle is 120mm; the electromagnetic stirring parameter of the crystallizer is 250A / 3Hz; the end electromagnetic stirring parameter is 350A / 8Hz.

[0056] Table 1

[0057]

[0058] During the continuous casting process of Example 1, a three-layer structure of a raw slag layer, a sintering layer, and a molten layer can be smoothly formed on the molten steel in the crystallizer, and the protective slag molten layer can flow normally between the crystallizer and the billet to play a sufficient lubricating role, ensuring that the billet can have a uniform billet shell of >10mm at the lower outlet of the crystallizer, reducing the incidence of pits and bubbles on the billet surface (i.e., the percentage of small square billets with pits or bubbles in the total number of square billets), and the incidence of billet surface depression is reduced to less than 0.5%. The production cost is saved, and after the billet is evenly cooled, the internal structure of the billet is improved, and the internal structure of the billet: the central shrinkage is 1.0 level, and the central crack is 0.5 level.

[0059] Comparative Example 1

[0060] This comparative example provides a method for producing a low-carbon free-cutting steel billet. The difference from Example 1 is that the tundish low-fire time is 60 min, the crystallizer copper tube taper is 0.40% / m, and the crystallizer cooling water is 135m 3 / h, using protective slag with physical and chemical properties as shown in Table 2, crystallizer vibration frequency = 100 + 50V (V is the pulling speed, V = 1.8m / min).

[0061] Table 2

[0062]

[0063]

[0064] In comparative example 1, the cooling of the ingot in the crystallizer was too strong and uneven during the production process, and the incidence of pits and bubbles on its surface was as high as 35%. The internal structure of the ingot was: the central shrinkage was level 1.5, and the central crack was level 1. The produced ingot was complained by the next process and could not be directly rolled and used. The surface of the ingot needed to be finished and ground before it could be put into use, which increased the production cost.

[0065] Comparative Example 2

[0066] This comparative example provides a method for producing low-carbon free-cutting steel billets, which is different from Example 1 mainly in that protective slag with physical and chemical performance indicators shown in Table 2 is used.

[0067] In Comparative Example 2, the ingot was cooled evenly in the crystallizer during the production process, the incidence of pits and bubbles on the surface of the ingot was as high as 30%, and the internal structure of the ingot had a central shrinkage of level 1.0 and a central crack of level 0.5.

[0068] Comparative Example 3

[0069] This comparative example provides a method for producing low-carbon free-cutting steel billets, which is different from comparative example 1 mainly in that protective slag with physical and chemical performance indicators shown in Table 1 is used.

[0070] In Comparative Example 3, the ingot was cooled uniformly in the crystallizer during the production process, the incidence of pits and bubbles on the surface of the ingot was as high as 10%, and the internal structure of the ingot had a central shrinkage of level 1.5 and a central crack of level 1.0.

[0071] By comparing Example 1 with Comparative Examples 1-3, it can be seen that by reasonably adjusting the composition of the protective slag and optimizing the baking parameters of the continuous casting machine ladle, the crystallizer copper tube and crystallizer vibration, the crystallizer cooling water volume parameters, etc., it is beneficial to improve the pit and bubble defects on the surface of the free-cutting steel ingot and improve the internal structure of the ingot.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A protective slag for low-carbon free-cutting steel, characterized in that: The protective slag includes the following components by weight percentage: SiO2 28wt%-35wt%, CaO 20wt%-26wt%, MgO 3wt%-6.5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 12wt%-15wt%, R2O 2wt%-5wt%, F 2.5wt%-5.5wt%, C 11wt%-12wt% and H2O 0.1wt%-0.35wt%, R2O is an oxide of alkali metal. The melting point of the protective slag is 1200℃-1300℃, the melt weight is 0.6g / ml-0.95g / ml, the viscosity is 1.3pa.s-1.8pa.s, and the basicity is 0.60-0.

80.

2. The protective slag for low-carbon free-cutting steel according to claim 1, characterized in that: The protective slag includes the following components by weight percentage: SiO2 30wt%-35wt%, CaO 20wt%-25wt%, MgO4wt%-5wt%, Fe2O3 0.6wt%-0.8wt%, Al2O3 13wt%-14wt%, R2O3.05wt%-3.95wt%, F 3.8wt%-4.2wt%, C 11wt%-12wt% and H2O 0.28wt%-0.32wt%. The melting point of the protective slag is 1248℃-1252℃, the melt weight is 0.84g / ml-0.86g / ml, the viscosity is 1.63pa.s-1.67pa.s and the basicity is 0.65-0.

75.

3. The protective slag for low-carbon free-cutting steel according to claim 1, characterized in that: The protective slag includes the following components by weight percentage: SiO2 33wt%, CaO 23wt%, MgO 4.5wt%, Fe2O3 0.7wt%, Al2O3 13.5wt%, R2O3.65wt%, F 4.0wt%, C 11.5wt% and H2O 0.30wt%. The melting point of the protective slag is 1250°C, the melt weight is 0.85g / ml, the viscosity is 1.65pa.s and the basicity is 0.

7.

4. A method for producing low-carbon free-cutting steel billets, characterized in that: The method comprises converter smelting, LF refining and continuous casting of small square billets using the protective slag described in any one of claims 1 to 3.

5. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: The low carbon free-cutting steel comprises, by weight percentage: C 0.03wt%-0.08wt%, Si≤0.08wt%, Mn 1.1wt%-1.5wt%, P0.05wt%-0.10wt%, S 0.20wt%-0.40wt%, Cu+Ni+As+Sn+Pb≤0.5wt%, and the balance is iron and unavoidable impurities.

6. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: In the continuous casting step, the tundish baking parameters are: low fire time ≥90min, medium fire time ≥0min, high fire time ≥60min, insulation time ≥60min, and total time 3.0h-4.5h.

7. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: In the continuous casting step, the vibration stroke of the crystallizer is 8mm-10mm, and the vibration frequency of the crystallizer is (79-81)*V times / min, where V is the pulling speed and the unit of the pulling speed is m / min.

8. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: The continuous casting step satisfies at least one of the following features af: a. The taper of the copper tube of the crystallizer is 0.15% / m-0.20% / m; b. Crystallizer cooling water flow rate is 105Nm 3 / h-120Nm 3 / h; c. The water gap of the crystallizer is controlled to be 4.0mm-4.5mm; d. The immersion nozzle adopts an integral type, the centering deviation between the immersion nozzle and the crystallizer is ≤±5mm, and the insertion depth of the immersion nozzle is 90mm-130mm; e. Crystallizer electromagnetic stirring parameters are 200-300A / 3Hz; f. The terminal electromagnetic stirring parameters are 300-400A / 8Hz.

9. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: The C content of the converter argon station is 0.04%-0.06%, and the free oxygen control range of the argon station is 30ppm-80ppm; And / or, the C content at the converter end point is greater than 0.08%, and the C content is adjusted to 85%-92% of the target C content during the steel tapping process.

10. The method for producing low-carbon free-cutting steel billets according to claim 4, characterized in that: The surface pit and bubble defect rate of the prepared small square billet is less than 0.5%.

Citation Information

Patent Citations

  • Continuous casting production technology for high-casting-speed preparation of low-carbon high-sulfur high-oxygen free-cutting steel

    CN110722119A

  • Design method of secondary cooling water in continuous casting process of high-carbon steel and preparation method of continuous casting billet

    CN111590043A

  • Method for improving surface quality of large-section low-carbon high-sulfur free-cutting steel casting blank

    CN115747623A

  • Mould for continuous casting of substantially polygonal strands

    EP0958871A1